2014
DOI: 10.3109/0284186x.2014.892211
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic training for the prevention of radiotherapy-induced trismus – a randomised study

Abstract: Background. Radiotherapy-induced trismus (RTIT) is a debilitating condition without any proven effective treatment. This study investigates the effectiveness of prophylactic training to prevent RTIT during and up to 12 months after completed RT in patients with head and neck cancer (HNC), also investigating the incidence of RTIT. Methods. Sixty-six consecutive patients from two RT clinics in Sweden were randomised into one of two groups: training with TheraBite ® Jaw Motion Rehabilitation System ™ or a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 14 publications
1
54
0
2
Order By: Relevance
“…Eight studies analyzed the effects of preventive measures on mouth opening, including with the TheraBite, active range of motion exercises (with or without chewing gum), and wooden tongue depressors …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies analyzed the effects of preventive measures on mouth opening, including with the TheraBite, active range of motion exercises (with or without chewing gum), and wooden tongue depressors …”
Section: Resultsmentioning
confidence: 99%
“…All studies reported the sample size, age, and sex of the participants, and premeasurements and postmeasurements of mouth opening. The risk of bias assessment that was performed for the included RCTs showed that many items were unclear (Table ). The criteria “overall incomplete data addressed” and “free of selective outcome reporting” were predominantly scored “yes.”…”
Section: Resultsmentioning
confidence: 99%
“…Prophylactic and immediate conservative management of trismus has been shown to be effective in some patients (Loorents et al, 2014; Cohen et al, 2005). The use of exercise therapy and jaw opening devices such as stacked tongue depressors, corkscrews, TheraBite and Dynasplint devices are routinely employed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, few studies have evaluated the effect of prophylactic exercise therapy on the development of trismus [32][33][34]. Considering the importance of the abovementioned aspect of time, prophylactic exercise therapy, starting before or during radiation treatment, might also be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of the abovementioned aspect of time, prophylactic exercise therapy, starting before or during radiation treatment, might also be valuable. Loorents et al [33] have indicated that prophylactic therapy is beneficial in only a small group of patients, being at risk for developing trismus. Two of these have demonstrated that jaw exercises can be useful in reducing [32] or preventing [34] the extent or severity of various side effects of radiotherapy-induced trismus.…”
Section: Discussionmentioning
confidence: 99%